2011
DOI: 10.1111/j.1742-481x.2011.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective use of negative pressure wound therapy provides quick wound‐bed preparation and complete graft take in the management of chronic venous ulcers

Abstract: Venous ulcers are characterised by longstanding and recurrent loss of skin integrity. Once occurred, healing is slow and recurrence is high because of inappropriate conditions of the wound bed. This study involves 20 patients with chronic venous ulcers at least 6 weeks of duration treated with negative pressure wound therapy (NPWT). Patients underwent a radical debridement of all devitalised tissues in the first operation. After adequate haemostasis, silver-impregnated polyurethane foam was applied. Once the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
0
20
0
1
Order By: Relevance
“…During dressing change, at the beginning of NPWT therapy; 3,4 During NPWT, at the end of therapy; 5,6 During dressing change, at the end of therapy;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During dressing change, at the beginning of NPWT therapy; 3,4 During NPWT, at the end of therapy; 5,6 During dressing change, at the end of therapy;…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The negative pressure wound therapy (NPWT) also known as the vacuum-assisted closure (VAC) is very fast developing method of the wounds treatment. It perfectly executes TIME rule (T-tissue debridement, I-infection and inflammation control, M -moisture balance and E -epidermalization stimulation).…”
Section: Introductionmentioning
confidence: 99%
“…The other complication of STSG over these structures is adhesions, limiting function and resulting in breakdown. Tendon-exposed wounds should be closed quickly to prevent tendon desiccation and resultant functional disability, but granulation tissue over tendon and ligament is difficult (24). Inducing granulation tissue over such structures requires additional wound bed preparation.…”
Section: Bioengineered Alternative Tissuesmentioning
confidence: 99%
“…With physical and occupational therapy, patients were able to attain an average range of motion in their skin grafted joints of the lower extremity that was 90.6% compared to their contralateral side. Yeong et al (24) reported on 23 patients with 33 wounds, in which artificial dermis was used to prepare tendon-exposed wounds for STSG, 11 of which were chronic ulcers. Thirty-nine percent of the patients had underlying diabetes mellitus, and 55% of the wounds were found in the lower extremities.…”
Section: Bioengineered Alternative Tissuesmentioning
confidence: 99%
“…A lot of researches were conducted to find out the benefits of skin grafting prior to the standard methods for treating trophic ulcers on the legs. They were looking for studies that tested whether the skin can increase the chance of healing in venous legs [6]. A number of studies show the advantage of using the skin flap, but there are no convincing differences and advantages in the application of various types of flaps [7].…”
Section: Introductionmentioning
confidence: 99%